EFFECT OF ANTISERUM ON THE ACTION OF SULFOBENZYLPENICILLIN - ITO, MASAKO; HOMMA, YUZURU (CHEMOTHERAPY, 1971)
It is known that antiserum is effective for prevention of Pseudomonas infection. Studies have been done on the effect of antiserum on the antibacterial activity of SB-PC using 3 strains of Pseudomonas aeruginosa against which MIC of SB-PC was 25, 50 and over 100 mcg/ml, respectively. Mice received antiserum subcutaneously and were challenged intraperitoneally with the live organism suspended in 5 % mucin one day or 6 hours after the administration of antiserum. Immediately after the challenge, SB-PC was given to the mice by the subcutaneous route in a single dose. A significant antiinfectious effect was evidenced by the concomitant administration of antiserum and SB-PC at such doses as do not prevent the death due to the infection in each single use. This indicates a possibility that the antibiotic might be effective in vivo against strains resistant in vitro if a trace amount of specific antibody is present in the host.